How much rugby is too much? A seven-season prospective cohort study of match exposure and injury risk in professional Rugby Union players - Williams, S.; Trewartha, G.; Kemp, S. P. T.; Brooks, J. H. M.; Fuller, C. W.; Taylor, A. E.; Cross, M. J.; Shaddick, G.; Stokes, K. A. (Sports Medicine, 2017)
Numerous studies have documented the incidence and nature of injuries in professional rugby union, but few have identified specific risk factors for injury in this population using appropriate statistical methods. In particular, little is known about the role of previous short-term or longer-term match exposures in current injury risk in this setting. Objectives: Our objective was to investigate the influence that match exposure has upon injury risk in rugby union. Method: We conducted a seven-season (2006/7-2012/13) prospective cohort study of time-loss injuries in 1253 English premiership professional players. Players` 12-month match exposure (number of matches a player was involved in for =20 min in the preceding 12 months) and 1-month match exposure (number of full-game equivalent [FGE] matches in preceding 30 days) were assessed as risk factors for injury using a nested frailty model and magnitude-based inferences. Results: The 12-month match exposure was associated with injury risk in a non-linear fashion; players who had been involved in fewer than ˜15 or more than ˜35 matches over the preceding 12-month period were more susceptible to injury. Monthly match exposure was linearly associated with injury risk (hazard ratio [HR]: 1.14 per 2 standard deviation [3.2 FGE] increase, 90% confidence interval [CI] 1.08-1.20; likely harmful), although this effect was substantially attenuated for players in the upper quartile for 12-month match exposures (>28 matches). Conclusion: A player`s accumulated (12-month) and recent (1-month) match exposure substantially influences their current injury risk. Careful attention should be paid to planning the workloads and monitoring the responses of players involved in: (1) a high (>˜35) number of matches in the previous year, (2) a low (<˜15) number of matches in the previous year, and (3) a low-moderate number of matches in previous year but who have played intensively in the recent past. These findings make a major contribution to evidence-based policy decisions regarding match workload limits in professional rugby union.